Increasing brand awareness of bank's mutual funds - Galang, Marc Justin L. (Animo Repository, 2021)
This Insider Action Research addressed the low level of brand awareness of a bank’s Mutual Funds. Communicating to clients need to be efficient and fast with the use of digital platforms, such as social media, emails, and webinars Our team was guided by several frameworks, particularly, the Customer Journey Mapping, Basic Design Principles, and Keller’s Brand Equity Model. For Cycle 1, our team maximized the use of available digital platforms through social media marketing, mainly Facebook. This online initiative was further supported by email marketing and development of marketing materials. To further increase our online presence, for Cycle 2, we incentivized clients who will take advantage of our available digital payment platforms. The results of this action research enabled our team to increase the public’s awareness of our bank’s Mutual Funds through the online channel.